Impact of 5-HT3 RA selection within triple antiemetic regimens on uncontrolled highly emetogenic chemotherapy-induced nausea/vomiting. (August 2011) - Schwartzberg, Lee; Jackson, James; Jain, Gagan; Balu, Sanjeev; Buchner, Deborah
Background: It is recommended that patients initiate triple antiemetic therapy with one of the 5-hydroxytryptamine receptor antagonists (5-HT3 RAs), aprepitant (or its intravenous prodrug fosaprepitant) and dexamethasone prior to the start of highly emetogenic chemotherapy (HEC). However, the impact of 5-HT3 RA selection within triple antiemetic regimens on the risk of uncontrolled chemotherapy-induced nausea and vomiting (CINV) with HEC has not been well studied.Aim: To assess the likelihood of an uncontrolled CINV event following antiemetic prophylaxis with the 5-HT3 RA palonosetron + aprepitant/fosaprepitant + dexamethasone (palonosetron cohort) versus any of the other 5-HT3 RAs + aprepitant/fosaprepitant + dexamethasone (other 5-HT3 RA cohort) among single-day HEC cycles.Methods: Single-day HEC cycles (a gap of at least 5 days between two administrations) among patients with a cancer diagnosis and receiving antiemetic prophylaxis with the aforementioned regimens between 1/1/2006 and 6/30/2010 were identified from the IMS LifeLink claims database. Uncontrolled CINV events were identified through ICD-9-CM codes (nausea and vomiting), Current Procedural Terminology codes (hydration), rescue medications and/or use of antiemetic therapy from days 2––5 following HEC administration. Risks for an uncontrolled CINV event among all patients, and within breast cancer and multiple cancer subpopulations, were analyzed at cycle level using logistic multivariate regression models.Results: A total of 8018 cycles for the palonosetron cohort and 1926 cycles for the other 5-HT3 RA cohort (3574 and 978 patients, respectively) were analyzed. Single-day HEC cycles received by the palonosetron cohort had a significantly lower unadjusted risk of an uncontrolled CINV event (17.5 vs 20.7% for the other 5-HT3 RA cohort; p = 0.0010), with a 17% lower adjusted risk for palonosetron-administered cycles (odds ratio: 0.83; 95% CI: 0.73––0.94; p = 0.0042). Results in the breast cancer and multiple cancer subgroups were consistent with those for the overall population.Conclusion: In this retrospective claims data analysis, single-day HEC cycles administered with palonosetron + aprepitant/fosaprepitant + dexamethasone had a lower risk for an uncontrolled CINV event versus other 5-HT3 RAs + aprepitant/fosaprepitant + dexamethasone.